Complete Regression of Giant Aneurysms in an Infant with Delayed Diagnosis and Refractory Kawasaki Disease via Combination Anticytokine Therapy: Case Report and Review of Similar Cases - Maegan Williams; Lakshmi Nagaraju; Mark Gorelik (Case Reports in Rheumatology)
Background. Kawasaki disease (KD) is an inflammatory vasculitis and is the most common cause of acquired childhood heart disease in developed countries. Current treatment with intravenous immunoglobulin (IVIG) is often ineffective in patients with delayed or refractory disease. We present a case of combination anticytokine therapy in an infant with delayed and refractory KD. Case Presentation. A 3-month-old infant presented with refractory KD with giant aneurysms after a delayed diagnosis of one month. Use of combination anticytokine therapy led to resolution of giant aneurysms over approximately 6 months. Conclusions. Our case is unique in effective use of anticytokine therapy in very delayed disease with giant aneurysms. Additionally, we review other cases for a broader perspective. Prospective study of anticytokine therapy for patients with giant aneurysms may be warranted.